Backdating the confirmed presence of Siphonaria pectinata (Gastropoda: Siphonariidae) along the northern Mediterranean shores, with a discussion on its status in the basin. Issue 1 (December 2016) - Crocetta, Fabio
Abstract Background The known historical range ofSiphonaria pectinata in the Mediterranean basin is unclear so far. Confirmed records come from the Strait of Gibraltar, the African coastline up to Algeria and the Spanish coastline up to Murcia/Valencia area, whilst all those published from additional Mediterranean areas are affected by a high degree of uncertainty. In addition, this taxon occurs in Tunisia (northern shores up to Cap Bon area), Greece (Saronikos Gulf) and Croatia (Split area), where it has been sighted only recently. The three latter records were widely discussed in the current literature due the possible rationale at the basis of the absence of past sightings, and there is a general agreement in considering that the Greek and Croatian records are the result of a human induced introduction. Results A literature overview on the Mediterranean distribution and alien statussensu lato of the striped false limpetSiphonaria pectinata is here provided for the first time. Concomitantly, the presence of this taxon in Croatia is here shown to date back to 1978 on the basis of material preserved in private collections, and at least to 1960–70 on the basis of local knowledge of Croatian malacologists and shell sizes of specimens collected in 1978. The findings reported in the present paper overall backdate by ca. 30–40 years the presence of this taxon in the Adriatic Sea, and also constitute the first confirmed record of the striped false limpet from the entire northern Mediterranean shores. Conclusions The present note corroborates the key role of citizen scientists in observing and recording variations in local biodiversity, as well as in contributing new and past distributional data, and concomitantly suggests the necessity of further work in the Mediterranean area to assess the local species distribution and pattern of spread before its designation as aliensensu lato .